Asymmetric Synthesis of Vicinally Bis(trifluoromethyl)-Substituted 3,3′-Pyrrolidinyl Spirooxindoles via Organocatalytic 1,3-Dipolar Cycloaddition Reactions - Zhu, Wen-Run; Zhang, Zhen-Wei; Huang, Wei-Hua; Lin, Ning; Chen, Qing; Chen, Kai-Bin; Wang, Bi-Chuan; Weng, Jiang; Lu, Gui (Synthesis, 2019)
Under bifunctional squaramide and thiourea organocatalysis, a series of vicinally bis(trifluoromethyl)-substituted 3,3′-pyrrolidinyl spirooxindoles were successfully synthesized via 1,3-dipolar cycloaddition reactions of 3-(trifluoroethylidene)oxindoles with diethyl 2-((2,2,2-trifluoroethyl)imino)malonate and N-(2,2,2-trifluoroethyl)isatin ketimines. The highlight of this protocol is the efficient construction of the vicinally bis(trifluoromethyl)-substituted pyrrolidine unit of spirooxindoles, including multiple contiguous stereogenic centres, in excellent yields and stereoselectivities.
Keywords: asymmetric catalysis; azomethine ylides; 1,3-dipolar cycloaddition; bis(trifluoromethyl)-substituted pyrrolidines; bifunctional organocatalysts